2019
DOI: 10.1002/jcp.29100
|View full text |Cite
|
Sign up to set email alerts
|

Type I collagen inhibits adipogenic differentiation via YAP activation in vitro

Abstract: Extracellular matrix (ECM) has a marked influence on adipose tissue development.Adipose tissue formation is initiated with proliferation of preadipocytes and migration before undergoing further differentiation into mature adipocytes. Previous studies showed that collagen I (col I) provides a good substratum for 3T3-L1 preadipocytes to grow and migrate. However, it remains unclear whether and how col I regulates adipogenic differentiation of preadipocytes. This study reports that lipid accumulation, representin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 59 publications
2
12
0
1
Order By: Relevance
“…In addition, YAP is activated in CAFs in response to mechanical stress, perturbation of the actin cytoskeleton and ECM stiffness [86,87]. Besides, the increased expression of YAP in preadipocytes is correlated with the repression of adipogenic differentiation processes [89]. Wang et al conducted a transcriptomic analysis to find that mesenchymal stromal/stem cell (MSC)-differentiated adipocyte exosomes activated the Hippo signaling pathway involved in two key downstream Hippo proteins YAP and TAZ in MCF-7 cells, while the Hippo pathway blockade could lead to reduced tumor growth [90].…”
Section: Extracellular Matrix Remodelingmentioning
confidence: 99%
“…In addition, YAP is activated in CAFs in response to mechanical stress, perturbation of the actin cytoskeleton and ECM stiffness [86,87]. Besides, the increased expression of YAP in preadipocytes is correlated with the repression of adipogenic differentiation processes [89]. Wang et al conducted a transcriptomic analysis to find that mesenchymal stromal/stem cell (MSC)-differentiated adipocyte exosomes activated the Hippo signaling pathway involved in two key downstream Hippo proteins YAP and TAZ in MCF-7 cells, while the Hippo pathway blockade could lead to reduced tumor growth [90].…”
Section: Extracellular Matrix Remodelingmentioning
confidence: 99%
“…On 2D culture, increasing YAP activity suppresses adipogenic differentiation [ 39 ]. In contrast, inactivation of YAP using small molecule or siRNA promotes adipogenic differentiation [ 40 ]. In a study using gelatin scaffolds with stiffness gradients from 8 kPa to 30 kPa, activation of YAP was found in the cells encapsulated in low-stiffness regions [ 36 ], similar to our findings here.…”
Section: Discussionmentioning
confidence: 99%
“…The research proposes the SB fibrils for scaffolds due to the diverse morphologies and good thermal characteristics [ 61 ]. Another recent work by Liu et al presents the lipid accumulation to proliferate the preadipocytes (3T3-L1) for development of adipose tissues [ 62 ]. The proliferation of preadipocytes is increased with the downregulation of Yes associated proteins (YAP) found in a cultured Type 1 collagen assay [ 62 ].…”
Section: Collagen Typementioning
confidence: 99%
“…Another recent work by Liu et al presents the lipid accumulation to proliferate the preadipocytes (3T3-L1) for development of adipose tissues [ 62 ]. The proliferation of preadipocytes is increased with the downregulation of Yes associated proteins (YAP) found in a cultured Type 1 collagen assay [ 62 ]. A similar nature of research is reported by the same author, but with a different research group [ 63 ], about the effects of collagen Type I on cell migration and differentiation through the culturing of mouse C2C12 myoblasts for skeletal muscle regeneration.…”
Section: Collagen Typementioning
confidence: 99%